Aqueous‐Phase Nitrile Hydration Catalyzed by an In Situ Generated Air‐Stable Ruthenium Catalyst. Issue 42 (2nd July 2019) - Ounkham, Whalmany L.; Weeden, Jason A.; Frost, Brian J.
Abstract: RuCl2 (PTA)4 (PTA = 1, 3, 5‐triaza‐7‐phosphaadamantane) is an active, recyclable, air‐stable, aqueous‐phase nitrile hydration catalyst. The development of an in situ generated aqueous‐phase nitrile hydration catalyst (RuCl3 ⋅3 H2 O+6 equivalents PTA) is reported. The activity of the in situ catalyst is comparable to RuCl2 (PTA)4 . The effects of [PTA] on the activity of the reaction were investigated: the catalytic activity, in general, increases as the pH goes up, which shows a positive correlation with [PTA]. The pH effects were further explored for both the in situ and RuCl2 (PTA)4 catalyzed reaction in phosphate buffer solutions with particular attention given to pH 6.8 buffer. Increased catalytic activity was observed at pH 6.8 versus water for both systems with turnover frequency (TOF) up to 135 h −1 observed for RuCl2 (PTA)4 and 64 h −1 for the in situ catalyst. Catalyst loading down to 0.001 mol % was examined with turnover numbers as high as 22 000 reported. Similar to the preformed catalyst, RuCl2 (PTA)4, the in situ catalyst could be recycled more than five times without significant loss of activity from either water or pH 6.8 buffer. Abstract : Made it in situ : The activity of an in situ generated catalyst from the commercially available RuCl3 and PTA is compared to RuCl2 (PTA)4 in water and in a pH 6.8 buffer. Both are active, air‐stable, recyclable, cyanide‐tolerant aqueous‐phase nitrile hydration catalysts.